NEW' DATA ON PLANKTONIC FORAMINIFERA BIOSTRATIGRAPHY FROM THE NEOGENE OF THE GARGANO PENINSULA (FOGGIA, SOUTHERN ITALY) - GIGLIOLA, VALLERI (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2020)
This paper concerns detailed analyses on planktonic foraminifera biostratigraphy of a section outcropping in the area of Poggio Imperiale, the western side of Gargano (FG) The sediments overlying the mesozoic carbonate platform have been assigned to Globorotalia puncticulata Zone (Early Pliocene) and to Globorotalia inflata Zone (Late Pliocene). A Middle Pliocene stratigraphic gap has been recognised.